Dilematika Penggunaan Klausul Arbitrase dalam Hukum Acara Indonesia terhadap Kontrak Bisnis Internasional - Seventina Monda Devita (Jurnal Hukum Lex Generalis, 2021)
Article 3 juncto. Article 11 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution states that parties using the Arbitration Clauses are not allowed to bring cases relating to the object of the agreement to the court. Not only that, but courts are also prohibited from accepting cases based on agreements that use the Arbitration Clauses. However, case No. 281/Pdt.G/2007/PN.Jkt.Pst and 238/Pdt.G/2005/PN.Jkt.Pst actually distorts the concept by examining and adjudicating the agreement contained in the arbitration clause. This could tarnish the face of Indonesian business law given that 90% of international commercial business contracts use arbitration clauses.